Influence of antiseptics on microcirculation after neuronal and receptor blockade - Goertz, Ole; Hirsch, Tobias; Ring, Andrej; Muehlberger, Thomas; Steinau, Hans U; Tilkorn, Daniel; Lehnhardt, Marcus; Homann, Heinz H (International wound journal, 2011)
The topical application of the antiseptics octenidine and polyhexanide on wounds seems to improve microcirculation. These two antiseptics were tested in combination with neuronal inhibition and sympathethic receptor blockade to verify these findings, explore the influence of β blockers on these microcirculative effects, and find out the principle of operation. Investigations were carried out on a standardised cremaster muscle model in rats (n = 66). The tested antiseptics, octenidine and polyhexanide were investigated alone (n = 12) and in combination with bupivacaine (n = 12), metoprolol (n = 12), phentolamine (n = 12) and surgical denervation (n = 12). Physiological saline was used for control (n = 6). The arteriolar diameter and functional capillary density (FCD) were investigated via trans-illumination microscopy before, as well as 60 and 120 minutes after application. Polyhexanide caused a significant increase in arteriolar diameter (86·5 ± 3·8 µm versus 100·0 ± 3·6 µm) and, like octenidine (7·2 ± 0·7 n/0·22 mm2 versus 11·6 ± 0·6 n/0·22 mm2), in FCD (9·2 ± 0·5 versus 12·6 ± 0·9) as well. When the antiseptics are used in combination with bupivacaine, metoprolol, phentolamine or surgical sympathectomy, these effects were eliminated or inverted. Assessing the results of the different blockades in combination with polyhexanide, we surmise that the antiseptic polyhexanide acts on the microcirculation mainly by blocking α receptors. This study shows that polyhexanide and octenidine improve muscular perfusion. Interestingly, the benefit of polyhexanide and octenidine on muscular perfusion is eliminated when the antiseptics are combined with other vasoactive agents, especially β blockers.